HAEMATOLOGICAL PROFILE AND PARASITOLOGICAL DIAGNOSIS OF TRYPANOSOMA VIVAX INFECTION IN SUDANESE NUBIAN GOATS - M. Osman, Nadia; Fadl, Mohamed; H. A/Rahman, Ahmed (Journal of Veterinary Medicine and Animal Production, 2022)
The present work was carried out to study the haematological profile and infectivity of a stock of Trypanosoma vivax which was isolated from an area outside tsetse zone to Nubian goats and their susceptibility to the infection. Different conventional parasitological techniques were also compared to diagnose the infection when taking blood samples from jugular and ear veins. Twenty Nubian goats aged 9-12 months were used in the experiment. Fifteen animals were experimentally infected with T. vivax stock, while five animals were served as uninfected control group. The study showed that Nubian goats are susceptible to T. vivax infection. The infection resulted in significant decrease in packed cell volume (PCV), total red blood cells counts (RBCs) and haemoglobin concentration (Hb) values. Significant increases were encountered in mean corpuscular volume (MCV) and mean corpuscular haemoglobin (MCH) values. No significant change was observed in mean corpuscular haemoglobin concentration (MCHC). These results indicated the presence of macrocytic normochromic anaemia. Total white blood cells (WBCs) counts were at normal range. The Haematocrit Centrifugation Technique and thin stained smears were found to be good diagnostic tools for T. vivax infection.